Tren Modern Perilaku Politik Nahdlatul Ulama (NU) di Era Multipartai Pasca Orde Baru: Kasus NU Jember, Jawa Timur: Modern Trends in the Political Behavior of Nahdlatul Ulama (NU) in the Post–New Order Multiparty Era: A Case Study of NU in Jember, East Java - Moh. Khusna Amal (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
Nahdlatul Ulama (NU) Jember’s political behavior has shifted significantly in the post-New Order multi-party era, moving from a cultural-political orientation toward practical, structural political engagement. This study examines this transformation using social action theory and the conceptual distinction between practical and cultural political behavior. The research analyzes key cases that illustrate NU Jember’s political shift, including its role in establishing the National Awakening Party (PKB), mobilizing mass support during the 1999 election, participating in the local vice-district head election, and participating in the formation of the Jember municipal government. A qualitative case study method was employed, with data collected through participant observation, in-depth interviews, documentation, and focus group discussions with NU Jember’s structural and cultural figures. The findings reveal that NU Jember’s increasingly intensive involvement in practical politics, both within and outside PKB, has prioritized short-term political gains over its social-religious role. The study concludes that this modern trend threatens NU Jember’s legitimacy as a socio-religious organization and recommends a return to its cultural-political khittah to maintain long-term democratic contribution. Perilaku politik Nahdlatul Ulama (NU) Jember mengalami pergeseran signifikan di era multi partai pasca Orde Baru, dari orientasi politik kultural menuju keterlibatan politik praktis-struktural. Penelitian ini mengkaji transformasi tersebut dengan menggunakan teori tindakan sosial serta paradigma perilaku politik praktis dan non-praktis. Tujuannya adalah menganalisis kasus-kasus kunci pergeseran politik NU Jember, meliputi partisipasi mendirikan PKB, mobilisasi massa pemilu 1999, keterlibatan dalam pemilihan bupati, dan pembentukan pemerintahan kota. Metode yang digunakan adalah studi kasus kualitatif melalui observasi partisipan, wawancara mendalam, dokumentasi, dan diskusi kelompok terfokus dengan tokoh struktural dan kultural NU Jember. Hasil penelitian menunjukkan bahwa intensitas keterlibatan NU Jember dalam politik praktis, baik melalui PKB maupun di luarnya, telah mengedepankan kepentingan politik sesaat dibandingkan peran sosial-keagamaannya. Kesimpulannya, tren modern ini mengancam legitimasi NU Jember sebagai organisasi sosial-keagamaan. Rekomendasinya, NU Jember perlu kembali memperkuat perilaku politik kulturalnya sesuai khittah 1926 demi kontribusi demokratis jangka panjang.